Spacer Cation Alloying in Ruddlesden-Popper Perovskites for Efficient Red Light-Emitting Diodes with Precisely Tunable Wavelengths - Qing, Jian (Advanced materials (Deerfield Beach, Fla.), 2021)
© 2021 The Authors. Advanced Materials published by Wiley-VCH GmbH.